1995
DOI: 10.1080/09540109509354886
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of the adjuvant capacity ofLactobacillus caseiand lipopolysaccharide on the intestinal secretory antibody response and resistance toSalmonellainfection in mice

Abstract: 1995) Comparative effect of the adjuvant capacity of Lactobacillus casei and lipopolysaccharide on the intestinal secretory antibody response and resistance to Salmonella infection in mice, Food and Agricultural Immunology, 7:3, 283-294, A comparative study was carried out to determine the effect of Lactobacillus casei lipopolysaccharide (LPS) and a mixture of L. casei plus LPS used as oral adjuvants on the increase of mucosal immunity. The ability of these substances to protect against enteric infection was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…It was reported that orally administered nonviable probiotics are less effective in modulating the immune system than viable probiotics due to their lower ability to bind to the intestinal mucosa (Perdigon et al 1995;Kato et al 1994), suggesting that probiotics should be viable in order to elicit beneficial health effects. However literature overview indicates that although viable probiotics have more documented health effects than nonviable probiotics, the latter are not without effect (Ouwehand and Salminen 1998;Čepeljnik et al 2007).…”
Section: Cfumentioning
confidence: 99%
“…It was reported that orally administered nonviable probiotics are less effective in modulating the immune system than viable probiotics due to their lower ability to bind to the intestinal mucosa (Perdigon et al 1995;Kato et al 1994), suggesting that probiotics should be viable in order to elicit beneficial health effects. However literature overview indicates that although viable probiotics have more documented health effects than nonviable probiotics, the latter are not without effect (Ouwehand and Salminen 1998;Čepeljnik et al 2007).…”
Section: Cfumentioning
confidence: 99%
“…Probiotics represent an economical alternative for boosting immune defenses and/or diminishing the severity of bacterial diarrhea. In several rodent studies, probiotics protected against infection with Salmonella Typhimurium [2,18,19]. Prolonged survival rates and diminished translocation of the pathogen to extraintestinal sites were correlated with a stimulation of adaptive immunity, clearly indicated by enhanced IgA production, a mucosal defense antibody [7].…”
Section: Innate Immunity á Intestinal Epithelial Cellmentioning
confidence: 99%
“…Shu et al (2000) and Gill et al (2001) reported that selected probiotic strains orally administered to mice conferred enhanced resistance against Salmonella enteritidis serovar Typhimurium infection. In our laboratory, it was demonstrated that the oral administration of milk fermented by Lactobacillus casei and Lactobacillus acidophilus (Perdigo´n et al, 1990), yoghurt (Perdigo´n et al, 1991) or its microflora and the strain L. casei CRL 431 itself (Perdigo´n et al, 1993(Perdigo´n et al, , 1995 were effective in the prevention of S. Typhimurium infection in conventional and in malnourished/ re-nourished mice (Gauffin-Cano and Perdigo´n, 2003). Not only fermented milks or lactic acid bacteria were reported to activate immune cells and to confer enhanced protection against enteropathogens.…”
Section: Introductionmentioning
confidence: 95%